Correlation of MRI and neuropathology in AIDS. - Everall, I P (1997)
OBJECTIVE: To assess the correlation between findings on radiological and neuropathological examinations of the brain. METHODS: The formalin fixed brains of 19 patients who had died of AIDS were examined by MRI and neuropathology. RESULTS: The rate of identification of cerebral atrophy was similar radiologically and neuropathologically. However, only in half of these cases were the two examinations concordant in the diagnosis. Furthermore, in the 15 brains which had radiological diffuse white matter lesions, the underlying pathology was heterogeneous. CONCLUSIONS: The possible reasons for the inconsistencies, and their relevance to the interpretation of imaging studies, are discussed. The study suggests that the qualitative identification of atrophy in the postmortem brain is problematical and that diffuse white matter lesions seen on MRI are not indicative of a specific pathological process.